Salafiyah and Khalafiyah Based Islamic Boarding Schools as Islamic Educational Institutions in Indonesia - Abddul Hakim Pohan; Ahmad Aziz; Muhammad Kosim (al-Afkar, Journal For Islamic Studies, 2025)
Islamic boarding schools are Islamic educational institutions that grow along with the development of Islam throughout the archipelago. A basic understanding of Islam and the Koran is the main goal. Islamic boarding schools are proliferating across the country in line with the changes, requiring Islamic boarding schools to modernize and update their curricula so that students leave with not only a religious but also a secular education. The institutional characteristics and definitions of Islamic boarding schools are discussed in this research. And this research is library research which aims to describe the development of Islamic boarding schools in Indonesia in terms of how Islamic boarding schools respond to traditions. The research results show that Islamic Boarding Schools in terms of how they respond to tradition are divided into three, namely Salafi, Khalafi, and Mujadi. Each Islamic boarding school has slightly different traditions. This difference is only in the emphasis on the tradition of studying classical books and the efforts of Islamic boarding schools in dealing with developments in science and technology.